Evaluating wetland soil carbon stability related to iron transformation during redox oscillations - Wang, Yiyun; Liu, Xiaoqing; Zhang, Xinying; Dai, Guohua; Wang, Zhiheng; Feng, Xiaojuan (Geoderma, 2022)
Redox shifts threaten to reduce the massive soil organic carbon (SOC) stocks in wetlands. However, ferrous iron [Fe(II)] oxidation may stabilize wetland SOC by reducing phenol oxidative activity, inhibiting CO2 emissions, and promoting SOC association with ferric Fe [Fe(III)] (oxyhydr)oxides. Yet the prevalence and efficacy of this mechanism are not clear. Here we select six contrasting soils from fens and bogs with different pH for microcosm incubation under cyclic redox conditions, with or without Fe(II) addition, and compared to static oxic incubation. CO2 emissions, microbial composition, enzyme activities, Fe species, and organic matter properties were measured to test the related mechanism. We found that compared to static oxic conditions, the response of Fe(II) to cyclic redox conditions (indicated by the response ratio of −0.48 to 0.53) was positively correlated with that of phenol oxidative activity and cumulative CO2 at the end of the incubation. Redox cycling had little effect on Fe-bound SOC (assessed by the modified citrate-bicarbonate-dithionite extraction), although Fe(II) addition increased Fe-bound SOC in all soils under cyclic redox owing to the production of short-range-ordered Fe(III) (oxyhydr)oxides (quantified by oxalate extraction). Furthermore, Fe(II) addition decreased CO2 emissions from three soils with pH > 6 but increased CO2 emissions from the Sphagnum-dominated soil, which had elevated Fe(II) levels after the incubation. These findings highlight the SOC stabilization potential of Fe(II) addition to wetland soils experiencing redox oscillations by promoting the accumulation of Fe-bound SOC as well as decreasing CO2 emissions (in response to phenol oxidative activity), especially in non-Sphagnum-dominated freshwater wetlands with relatively high pH.
Keywords: Bog; CO emissions; Cyclic redox; Fen; Iron-bound organic carbon